Zinc sorption characteristics and release kinetics from soils with long-term zinc and phosphorus application - SINGH, PARMINDER; SAINI, SAT PAL; SINGH, PRITPAL (The Indian Journal of Agricultural Sciences, 2020)
We investigated the effect of long-term phosphorus (P) and zinc (Zn) application in three soils (Soil-I, Soil-II and Soil-III) with differential P content on Zn sorption and release kinetics to understand the underlying mechanism controlling Zn sorption-desorption reactions. Zn sorption was highest in soil-III (54.4-96.4% of added Zn), and was the lowest in soil-I (44.1-94.3% of added Zn) in no-P applied soils. In soil-III, 60.6-97.6% of applied Zn gets sorbed on soil colloidal complex with P application at 100 mg P kg-1, which was 1.2-11.4% higher at differential levels of Zn application. Results showed that Langmuir sorption maxima (b) and Freundlich’s adsorptive capacity (Y) were lowest for soil-I without P application and was the highest in soil-III with P application. These results suggests that soil-III with P application at 100 mg P kg-1 with highest Zn sorption had the lowest Zn release capacity. Further, these results showed that Elovich equation best described the kinetics of Zn release from three soils with highest value of coefficient of determination (R2=0.93-0.98*, p<0.05) and lowest standard error (S.E.= 0.172-0.256).